Innovative Security Solutions for Information Technology and Communications : 12th International Conference, SecITC 2019, Bucharest, Romania, November 14-15, 2019, Revised Selected Papers /: 12th International Conference, SecITC 2019, Bucharest, Romania, November 14-15, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available